Experimental and analytical studies of reinforced concrete short beams at elevated temperatures - Fan, Shengxin (2022)
This paper presents an experimental and analytical programme conducted on a total of seven reinforced concrete (RC) short beams, including one test at ambient temperature and six others at elevated temperatures. This study investigates experimentally the behaviour of RC short beams when subjected to elevated temperatures under the effect of shear-span-to-effective-depth (a/d) ratio and thermal-induced axial restraint. From the literature, this type of study on short beams has not been conducted before. It is experimentally shown that, for unrestrained short beams, as a/d increases, mid-span deflections at failure also increase and failure mode changes from diagonal splitting to shear tension. Besides, the influence of axial restraint on short beams is dependent on a/d ratio. For short beams of small a/d ratios (a/d ≤ 2.00), axial restraint increases mid-span deflections and flexural cracking, whereas it restrains deflections and shortens the failure duration of short beams with a/d ratio of 2.50. Furthermore, regardless of a/d, addition of axial restraint generally shifted the failure mode to a more brittle shear mode at elevated temperatures. Secondly, a simplified analytical model based on strut-and-tie-model (STM) is proposed and verified with test data to predict the performance of RC short beams at high temperatures. This model is applicable to both axially-restrained and unrestrained short beams subjected to elevated temperatures. The proposed STM is capable of providing consistently conservative and safe predictions of temperature profile, axial restraint force, load-carrying capacity and failure duration.